The INFLUENCE OF ORGANIZATIONAL COMMITMENT AND EMPLOYEE RETENTION ON PRODUCTION EMPLOYEE TURNOVER INTENTION AT PT. BENGKALIS DOCKINDO PERKASA - Nurlasera, Nurlasera; Alfianti, Devi; Mahyarni, Mahyarni; Julina, Julina (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to determine the effect of organizational commitment and employee retention on the turnover intention of production employees at PT. Bengkalis, Dockindo Perkasa, Sungai Siput Village, Bengkalis Regency. This research method uses a quantitative approach. The population in this study is PT. Bengkalis Dockindo Perkasa. The sample used was 98 employees. The data collection method in this study used questionnaires and the data analysis used was multiple linear regression through the SPSS program version 23. The results of this study show that: (1) organizational commitment negatively affects turnover intention, with regression coefficient value – 0.232, t value calculated – 2.493 (sig 0.014 < 0.05). (2) Employee retention negatively affects turnover intention, with regression coefficient value -0.119, calculated t value -2.189 (sig 0.031< 0.05). The conclusion of this study is that organizational commitment and employee retention negatively affect the turnover intention of production employees at PT. Bengkalis, Dockindo Perkasa, Sungai Siput Village, Bengkalis Regency.